2020
DOI: 10.1111/aji.13232
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic immune biomarkers as risk factors in women with different symptoms of threatened late miscarriage

Abstract: Problem:To investigate risk factors that can help identify the possibility of pregnancy loss in threatened late miscarriage (TLM) patients with and without spontaneous uterine contractions. Method of study:Amniotic immune biomarkers (IL2β receptor, IL6, IL8, IL10, IL1β, and TNFα) were assayed, and "sludge" was assessed. Patients without intrauterine infections were treated and followed up until delivery, and pregnancy outcomes were recorded. The two groups were compared for the differences in biomarker levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Studies have shown that genetic factors play an important role in early miscarriage, with about 50% of the cases caused by chromosomal abnormalities (van den Berg et al, 2012;Ozawa et al, 2019), while the risk factors of late miscarriage (≥28 gestational weeks) are mainly immune and environmental factors (Meng et al, 2020). Types of chromosomal abnormalities including numerical chromosomal abnormality, structural chromosomal abnormality, chimera, and polyploidy.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that genetic factors play an important role in early miscarriage, with about 50% of the cases caused by chromosomal abnormalities (van den Berg et al, 2012;Ozawa et al, 2019), while the risk factors of late miscarriage (≥28 gestational weeks) are mainly immune and environmental factors (Meng et al, 2020). Types of chromosomal abnormalities including numerical chromosomal abnormality, structural chromosomal abnormality, chimera, and polyploidy.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that genetic factors play an important role in miscarriage, with 50% of cases caused by chromosomal abnormalities [ 18 ]. On the other hand, the risk factors for stillbirth (≥ 28 gestational weeks) are mainly immune and environmental factors [ 19 ]. Researchers have found that fetal chromosomal aneuploidy is the primary cause of miscarriage [ 20 ], with aneuploidy of chromosomes 13, 16, 18, 21, 22 and sex chromosomes being ubiquitous [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Late miscarriage (LM), also known as second‐trimester or mid‐trimester pregnancy loss, is defined differently across countries 1 . In China, LM refers to a complete pregnancy loss between 12 and 28 weeks of gestation.…”
Section: Introductionmentioning
confidence: 99%
“…
Late miscarriage (LM), also known as second-trimester or midtrimester pregnancy loss, is defined differently across countries. 1 In China, LM refers to a complete pregnancy loss between 12 and 28 weeks of gestation. According to a previous retrospective study, 2 the main causes of LM include cervical incompetence, fetal anomaly, maternal infection, and premature rupture of membranes.
…”
mentioning
confidence: 99%